PEMANFAATAN ANDROID PADA SISTEM PRESENSI KARYAWAN DI PT. GESCHOOL CERDAS MANDIRI - Tamatjita, E.N.; Kusumaningrum, Angraini; Ardianto, Ade Ari (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2016)
Presence is the most important activity, because it is related to productivity of employees and one part of human resources control indicator which aim to improve the potential of human resources itself. The function of presence programme is for knowing presence of employees by used android smartphone. The employees can entry their presence data by use the presence programme, they just need to touch the attendance button, check out from office button and also take a leave button, the result of entry data will be entered into database system in the form of an admin web. The function of the web is to determine the employees data entry and add employees data. The employees should used android smartphone with same wifi local area of the company that used also by the admin web because it became the benefits of local wifi. In this case we need three days for trial, with a wide range of trials from 10 users testing, 10 smartphones testing, access point testing, blackbox testing and also white box testing. The aim of user testing is done by employees with android smartphone is to know does the time result of entry data equal with the time result of admin in web. Smartphone trial by the employees is done by view notification alerts presence was accepted by the admin, the result show if the average is less than 20 seconds. Access point trial done by the admin, is to show the speed of access point received by androind smartphone is less than 10 seconds. Black box trial and white box trial done by admin, the flow of the web, and also the flow of android smartphone program get the 100%. The result of three days trial finds that everything in presence program is going well.